1960
DOI: 10.1063/1.1730924
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Study of Gaseous Molybdenum, Tungsten, and Uranium Oxides

Abstract: Partial pressures of the gaseous oxides MoO, MoO2, MoO3, WO, WO2, WO3, UO, UO2, and UO3 in the systems Mo–Al2O3 and U–Al2O3 have been measured by mass spectrometric methods. The vapor pressure of uranium has also been determined. The reaction enthalpies derived from these measurements are: Reaction         ΔH0ο kcal/moleMoO(g)→Mo(g)+O(g)         116±15MoO2(g)→Mo(g)+2O(g)         262±10MoO3(g)→Mo(g)+3O(g)         411±7WO(g)→W(g)+O(g)         154±10WO2(g)→W(g)+2O(g)         296±7WO3(g)→W(g)+3O(g)         443±7UO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

1962
1962
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(30 citation statements)
references
References 11 publications
5
25
0
Order By: Relevance
“…These proportions can be changed by oxidation or deoxidation with surface reactions depending on the cell and furnace materials together with the quality of the vacuum system. Usually as observed by De Maria et al [74], Pattoret, Drowart and Smoes [59,61,62], and Storms [63] these contribution for the U-O system are more pronounced for reductive species (U > UO > UO 2 ). Indeed Pattoret and coworkers did not detect any contribution for UO 2 (g), with their mobile slit device, and the UO 2 'slit profile' served as a reference (see Fig.…”
Section: Knudsen Cell and Mass Spectrometric Determinationsmentioning
confidence: 61%
See 3 more Smart Citations
“…These proportions can be changed by oxidation or deoxidation with surface reactions depending on the cell and furnace materials together with the quality of the vacuum system. Usually as observed by De Maria et al [74], Pattoret, Drowart and Smoes [59,61,62], and Storms [63] these contribution for the U-O system are more pronounced for reductive species (U > UO > UO 2 ). Indeed Pattoret and coworkers did not detect any contribution for UO 2 (g), with their mobile slit device, and the UO 2 'slit profile' served as a reference (see Fig.…”
Section: Knudsen Cell and Mass Spectrometric Determinationsmentioning
confidence: 61%
“…The reactivity of the U-O system is also relevant outside the effusion cells, since many authors observed parasitic molecular flows additional to the genuine effusion flow that is the only flow appropriate to the studied equilibrium. In original and earlier mass spectrometric devices, as for instance in the study of gaseous U-O system, De Maria et al [74] observed with a mobile slit interposed between the effusion orifice and the ion source aperture that surface vaporizations (Fig. 12(c)) contributed to the detected flow; the more reducing the original vapour, the more additional contribution was observed.…”
Section: Knudsen Cell and Mass Spectrometric Determinationsmentioning
confidence: 93%
See 2 more Smart Citations
“…In 1959, DeMaria et al 10 in a Knudsen-effusion massspectrometric study used an extrapolation of the ionization efficiency curve to obtain an ion-appearance potential of IP͑MoO͒ϭ8.0Ϯ0.6 eV. Finally, using the density functional calculation mentioned above Broclawik 49 determined the IP͑MoO͒ to be near 8.03 eV.…”
Section: Moomentioning
confidence: 99%